2007
DOI: 10.1596/1813-9450-4410
|View full text |Cite
|
Sign up to set email alerts
|

Current Debates On Infrastructure Policy

Abstract: The findings, interpretations, and conclusions expressed herein do not necessarily reflect the views of the sponsoring organizations or the governments they represent. The sponsoring organizations do not guarantee the accuracy of the data included in this work. The boundaries, colors, denominations, and other information shown on any map in this work do not imply any judgment on the part of the sponsoring organizations concerning the legal status of any territory or the endorsement or acceptance of such bounda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
72
0
7

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(80 citation statements)
references
References 76 publications
(70 reference statements)
1
72
0
7
Order By: Relevance
“…Even though investments in the respective infrastructures are likely to yield large returns (Calderon and Serven, 2014), in the absence of stable institutions and without access to capital markets it is unlikely that these public goods will be provided at the socially desirable level (Estache and Fay, 2007). As a result, infrastructure access gaps -especially within the developing world -are still high (see section 3.1 for details).…”
Section: Introductionmentioning
confidence: 99%
“…Even though investments in the respective infrastructures are likely to yield large returns (Calderon and Serven, 2014), in the absence of stable institutions and without access to capital markets it is unlikely that these public goods will be provided at the socially desirable level (Estache and Fay, 2007). As a result, infrastructure access gaps -especially within the developing world -are still high (see section 3.1 for details).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, he points out that infrastructure can exacerbate inequality, in part because of its unfair allocation, but also because the well-off are better positioned to take advantage of the economic opportunities it creates. Similarly, Estache and Fay (2007) showed that access to infrastructure was highly skewed against the poorest. This reflects lack of physical access as well as limited affordability.…”
Section: Public Spending On Physical Infrastructurementioning
confidence: 99%
“…The development of infrastructure has been proven to be an effective means for economic progress (Estache and Fay 2007). Thus, it has been shown that the quantity and quality of the infrastructure have a positive impact on economic growth and are negatively correlated to income inequality.…”
Section: Introductionmentioning
confidence: 99%